A REVIEW ON IMPACT OF STRESS ON THE WELL BEING OF COLLEGE STUDENTS - Komal, .; Vandana, . (INTI International University, 2023)
Stress represents a state of psychological unease experienced by individuals with meticulous personalities, stemming from challenges within their environmental and social spheres, and often resulting in a range of health issues. The period of adolescence emerges as a pivotal phase, characterized by substantial life changes for students. In today's modern era, students navigate an exceedingly competitive world that places significant stressors on them, demanding their adaptation for survival. Stress emerges as an inevitable facet across all facets of human existence, creating emotional imbalances among students for various reasons including academic evaluations, assignments, and the competitive nature within their chosen fields. Additionally, concerns about financial matters related to education and future employment prospects contribute to this stress. In light of these considerations, a comprehensive research review was conducted to gauge the magnitude of stress, identify its causative factors, and discern its multifaceted impacts. Based on the existing study this research reveals an array of environmental, social, and personal triggers responsible for the stress experienced by college students. Moreover, the ramifications extend to their physical and mental well-being, profoundly impacting their holistic development.